Hypomethylation and Over-Expression of the Beta Isoform of BLIMP1 is Induced by Epstein-Barr Virus Infection of B Cells; Potential Implications for the Pathogenesis of EBV-Associated Lymphomas - Vrzalikova, Katerina; Leonard, Sarah; Fan, Yichao; Bell, Andrew; Vockerodt, Martina; Flodr, Patrik; Wright, Kenneth L; Rowe, Martin; Tao, Qian; Murray, Paul G (Pathogens (Basel, Switzerland), 2012)
B-lymphocyte-induced maturation protein 1 (BLIMP1) exists as two major isoforms, α and β, which arise from alternate promoters. Inactivation of the full length BLIMP1α isoform is thought to contribute to B cell lymphomagenesis by blocking post-germinal centre (GC) B cell differentiation. In contrast, the shorter β isoform is functionally impaired and over-expressed in several haematological malignancies, including diffuse large B cell lymphomas (DLBCL). We have studied the influence on BLIMP1β expression of the Epstein-Barr virus (EBV), a human herpesvirus that is implicated in the pathogenesis of several GC-derived lymphomas, including a subset of DLBCL and Hodgkin's lymphoma (HL). We show that BLIMP1β expression is increased following the EBV infection of normal human tonsillar GC B cells. We also show that this change in expression is accompanied by hypomethylation of the BLIMP1β-specific promoter. Furthermore, we confirmed previous reports that the BLIMP1β promoter is hypomethylated in DLBCL cell lines and show for the first time that BLIMP1β is hypomethylated in the Hodgkin/Reed-Sternberg (HRS) cells of HL. Our results provide evidence in support of a role for BLIMP1β in the pathogenesis of EBV-associated B cell lymphomas.